STUDENTS' PERCEPTIONS OF USING E-COMICS AS A MEDIA IN MATHEMATICS LEARNING - Yulinar Safitri; Mailizar Mailizar; Rahmah Johar (Jurnal Infinity, 2021)
The development of technology in education greatly influences learning strategies. Thus, teachers must adapt and present interesting and technology-based learning, such as e-comics. Therefore, the teacher must see in advance the extent to which students will accept e-comics for use in learning mathematics. This research aimed to determine students' perceptions of the use of e-comics as a media in mathematics learning. This research implemented a quantitative approach with a survey method. The samples were 124 students of Junior High Schools (SMP / MTs) in Aceh. The research data were obtained from questionnaires filled by students which were collected through the TAM (Technology Acceptance Models) framework which was distributed online.  The results showed that students used e-comic as a learning media influenced by their perceived benefits and attitudes towards the use of e-comic. The perceived benefits of students' attitudes have a significant role in their behavioral intention to use e-comic in learning mathematics. This research implies that e-comics has the potential to be used as a media in mathematics learning, especially on material that is considered difficult so that it can attract students' attention.